Toward implementing the marine spatial planning approach in the Egyptian marine areas - Mamdouh Awad Abdelrahman Shahhat (Maritime Research and Technology)
The blue economy notion is how to use the maritime resources in sustainable way. Egypt owns a large coastline extends for 3000 km. in addition, Egypt has dedicated its marine regions for different uses. Moreover, the Egyptian marine regions are divided into traditional areas (shipping routes, and fisheries) and new areas (oil and gas explorations, and fish farms). However, there is conflicts between stakeholders either user to user or user and marine environment.  As  a results of majors drawbacks found in implementing MPAs, and ICZM  in Egypt, the maritime spatial planning approach is a suitable marine ecosystem management tool to resolve conflicts between ocean users and it an appropriate tool in hand decision makers to enable Egypt in achieving the sustainable development goals. While adopting the maritime spatial planning initiative in Egypt requires four main conditions, stakeholders’ engagement in the MSP process from beginning, binding legally framework, designated ministry, and suitable monitoring and evaluation.    The aim of this research paper is to examine last papers for the MSP approach to present ideal policies for decision-makers, stakeholders, and academic researchers to know about the possibilities, challenges, and mitigation steps of adopting the MSP approach in Egypt. This paper will be a significant data hub about MSP in Egypt because there is no research papers have adopted the MSP initiative in Egypt. Keywords: MSP, ICZM, MPAs, SDGs, climate change, CCS   Received: 11 April 2023 Accepted: 01 July 2023 Published : 20 July 2023